Statin prescriptions and progression of advanced fibrosis risk in primary care patients with MASLD - Andrew D Schreiner; William P Moran; Jingwen Zhang; Patrick D Mauldin; Justin Marsden; Mulugeta Gebregziabher; Chelsey A Petz; David G Koch; Chloe Bays (BMJ Open Gastroenterology)
Objective We aimed to determine the association of statins with progression to a high risk for advanced fibrosis in primary care patients with metabolic dysfunction-associated steatotic liver disease (MASLD).Design This retrospective cohort study of electronic health record data included patients with MASLD and an initial low or indeterminate risk for advanced fibrosis, determined by Fibrosis-4 Index (FIB-4) score (<2.67). Patients were followed from the index FIB-4 until the primary outcome of a high-risk FIB-4 (≥2.67) or the end of the study period. Prescription for a statin during follow-up was the primary exposure. We developed Cox regression models for the time to a high-risk FIB-4 score with statin therapy as the primary covariate and adjusting for baseline fibrosis risk, demographic and comorbidity variables.Results The cohort of 1238 patients with MASLD was followed for a mean of 3.3 years, with 47% of patients receiving a prescription for a statin, and 18% of patients progressing to a high-risk FIB-4. In the adjusted Cox model with statin prescription as the primary exposure, statins were associated with a lower risk (HR 0.60; 95% CI 0.45 to 0.80) of progressing to a FIB-4≥2.67. In the adjusted Cox models with statin prescription intensity as the exposure, moderate (HR 0.60; 95% CI 0.42 to 0.84) and high intensity (HR 0.61; 95% CI 0.42 to 0.88) statins were associated with a lower risk of progressing to a high-risk FIB-4.Conclusion Statin prescriptions, and specifically moderate and high intensity statin prescriptions, demonstrate a protective association with fibrosis risk progression in primary care patients with MASLD.